Heart Rate Kinetics and Sympatho-Vagal Balance Accompanying a Maximal Sprint Test - Storniolo, Jorge L.; Esposti, Roberto; Cavallari, Paolo (Frontiers in Psychology, 2020)
When a maximal sprint starts, the Heart Rate (HR) quickly increases. After the exercise ends, HR keeps high for seconds before recovering with a roughly exponential decay. Such decay and its time constant (off) have been widely studied, but less attention was devoted to the time delay (Tdelay) between sprint end and HR decay onset. Considering the correlation between sympatho-vagal balance and performance, as well as the occurrence of heart failure in cardiopaths during the post-exercise phase, we evaluated sympatho-vagal balance before and after sprint, trying to correlate it with both Tdelay and TAUoff. R-R intervals, recorded in 24 healthy adults from 5 min before to 5 min after a 60-m sprint-test (from Storniolo et al., 2017, with permission of all Authors), were re-processed to extract HR variability power (LF and HF) in the low and high frequency ranges, respectively. The sympatho-vagal balance, evaluated in pre-test resting period (LF/HF)REST and at steady-state recovery (LF/HF)RECOV, was correlated with Tdelay and TAUoff. Both (LF/HF)REST and (LF/HF)RECOV had a skewed distribution. Significant rank correlation was found for (LF/HF)REST vs. TAUoff and for (LF/HF)RECOV vs. both TAUoff and Tdelay. The difference (LF/HF)RECOV-REST had a normal distribution and a strong partial correlation with Tdelay but not with TAUoff. Thus, a long Tdelay marks a sympathetic activity that keeps high after exercise, while an high sympathetic activity before sprint leads to a slow recovery (high TAUoff), seemingly accompanying a poor performance.